2016
DOI: 10.1007/s10404-016-1787-1
|View full text |Cite
|
Sign up to set email alerts
|

Sorting algal cells by morphology in spiral microchannels using inertial microfluidics

Abstract: simplicity of inertial microfluidics make it appropriate for the high-throughput pre-sorting of algae cells upstream of other integrated sensing modalities in a field-deployable device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 41 publications
0
36
0
Order By: Relevance
“…With regard to shape-based separation of candida cells using our device, it was confirmed that separation efficiency is affected by asymmetry due to the shape of the formed germ tube. In other studies, the device enables the separation of cells based on shape differences without curvature, which can be a useful biomarker indicating cell type, cell cycle, and differences based on environmental conditions (e.g., fungal pathogens, microalgae, and rod-shaped bacteria (e.g., bacilli)) [34,46,47,68]. In addition, additional numerical analyses and simulations are required to calculate the elastic force exerted on nonspherical particles/cells and to predict the flow characteristics of those in the viscoelastic fluid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to shape-based separation of candida cells using our device, it was confirmed that separation efficiency is affected by asymmetry due to the shape of the formed germ tube. In other studies, the device enables the separation of cells based on shape differences without curvature, which can be a useful biomarker indicating cell type, cell cycle, and differences based on environmental conditions (e.g., fungal pathogens, microalgae, and rod-shaped bacteria (e.g., bacilli)) [34,46,47,68]. In addition, additional numerical analyses and simulations are required to calculate the elastic force exerted on nonspherical particles/cells and to predict the flow characteristics of those in the viscoelastic fluid.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a viscoelastic sheathless shape-based separation technique has been applied to drug-treated human fungal pathogens using differences in morphology [46]. However, there is still room for improvement in device throughput and applications to various biological particles with different shapes [34,47].…”
Section: Introductionmentioning
confidence: 99%
“…Son et al employed inertial separation in the curved microchannel to purify sperm cells from RBCs and leukocytes [300,301]. Schaap et al first demonstrated the microfluidic separation of three specimens of algal cells of various sizes and shapes, including non-spherical ones [302]. Lee et al used inertial separation in the curved channel for mesenchymal stem cell enrichment from a tissue-digested mouse bone marrow cell mixture [303].…”
Section: Inertial Focusing In Microfluidic Channelsmentioning
confidence: 99%
“…They can simulate small-scale fluid flow and chemical gradients and offer full manual control over the particles to study the desired details, e.g., for food market, clinical, pharmaceutical, and other applications [1][2][3][4][5][6][7]. Precise manipulations such as focusing, separation, and fractionation of cells is a vital capability of microfluidics which can be achieved by engineering hydrodynamics forces based on unique physical attributes of cells such as size [8,9], density [9,10], deformability [11][12][13], and morphology [14] using variety of methods such as crossflow filtration [15], electrode arrays [16], optical force switching [17] and other methods, some of and other methods, some of which can be found in detail in the review presented in [18]. In this spirit, hydrodynamic phenomena, which carry microenvironmental physical impacts on cells, are critical in almost all physiological functions and bodily systems.…”
Section: Microfluidic Systems For Cellular Flow Manipulationmentioning
confidence: 99%